A General Equilibrium Model of International Portfolio Choice - UPPAL, RAMAN (Journal of Finance, 1993)
ABSTRACT We investigate, in a two‐country general equilibrium model, whether a bias in consumption towards domestic goods will necessarily lead to a preference for domestic securities. We develop a model where investors are constrained to consume only from their domestic capital stock and where it is costly to transfer capital across countries. In this model, investors less risk averse than an investor with log utility bias their portfolios towards domestic assets. Investors more risk averse than log, however, prefer foreign assets. Thus, this model suggests that it is unlikely that the portfolios observed empirically can be explained by the high proportion of domestic goods in total consumption.